2015
DOI: 10.1080/10627197.2015.1028622
|View full text |Cite
|
Sign up to set email alerts
|

Construct Relevant or Irrelevant? The Role of Linguistic Complexity in the Assessment of English Language Learners’ Science Knowledge

Abstract: This article addresses the issue of language-related construct-irrelevant variance on content area tests from the perspective of systemic functional linguistics. We propose that the construct relevance of language used in content area assessments, and consequent claims of construct-irrelevant variance and bias, should be determined according to the degree of correspondence between language use in the assessment and language use in the educational contexts in which the content is learned and used. This can be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 24 publications
(78 reference statements)
2
14
0
Order By: Relevance
“…Unlike technical vocabulary-which are the specialized words specific to a discipline, academic vocabulary words are more generalized and span across many content areas (Stevens, Butler, & Castellon-Wellington, 2001). This distinction is important for many studies investigating the language effects of content assessments because while technical vocabulary is deemed to be construct-relevant, academic vocabulary is often seen as constructindependent and, subsequently, may interfere with the interpretations of student scores on assessments (Avenia-Tapper & Llosa, 2015;Haag, Roppelt, & Heppt, 2015;Wolf and Leon, 2009). Coxhead's (2000) academic word list (AWL) is used here to identify academic words on the assessment 3 .…”
Section: Item Features For the Learning Progressions In Middle Schoolmentioning
confidence: 99%
“…Unlike technical vocabulary-which are the specialized words specific to a discipline, academic vocabulary words are more generalized and span across many content areas (Stevens, Butler, & Castellon-Wellington, 2001). This distinction is important for many studies investigating the language effects of content assessments because while technical vocabulary is deemed to be construct-relevant, academic vocabulary is often seen as constructindependent and, subsequently, may interfere with the interpretations of student scores on assessments (Avenia-Tapper & Llosa, 2015;Haag, Roppelt, & Heppt, 2015;Wolf and Leon, 2009). Coxhead's (2000) academic word list (AWL) is used here to identify academic words on the assessment 3 .…”
Section: Item Features For the Learning Progressions In Middle Schoolmentioning
confidence: 99%
“…Researchers have expressed concern that such tests may introduce additional English language demands that are not part of the constructs the tests are intended to measure, and that these demands may differentially affect EL test-takers (Abedi & Linquanti, 2012). Others have argued that the English language demands of science tests written in English are part of the construct that science tests are intended to measure, if the language of test items is consistent with the language of the discipline (Avenia-Tapper & Llosa, 2015). While we believe that some forms of language are appropriate targets of instruction, we do not believe that interpreting and producing complex academic language in English is the only way in which students can communicate about science, even though many testing regimes limit the ways students can demonstrate this ability.…”
Section: The Language Of Science Testsmentioning
confidence: 99%
“…A significant body of research reveals that high-stakes assessments present a challenge for ELs [6][7][8][9][10][11][12][13][14][15][16][17]. Research points to three significant issues that impact the assessment of ELs.…”
Section: Introductionmentioning
confidence: 99%
“…This assertion is supported by research that established a strong association between increasing linguistic complexity and decreasing test performance [7]. Second, a growing body of research demonstrates that ELs' test performance is reflective of their English language attainment versus their content knowledge [8][9][10]. As a case in point, in a study with 1700 ELs who were tested in English and Spanish on a standardized math achievement test, the results showed that the ELs answered more items correctly on a math test in their home language [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation